The quest for effective interdisciplinary graduate supervision: A critical narrative analysis - Hibbert, Kathryn M; Lingard, Lorelei; Vanstone, Meredith; Kinsella, Elizabeth Anne; McKenzie, Pam; Wilson, Timothy D.; Pitman, Allan (Canadian Journal of Higher Education, 2014)
Interdisciplinarity is a pervasive trend in 21st-century knowledge building and innovation. It is predicated on the recognition that creative solutions to the world’s increasingly complex problems require the intersection of diverse expertise. Little scholarly attention has been directed towards how the new interdisciplinary (ID) model is influencing the processes and outcomes of graduate research training. In a qualitative study informed by critical narrative analysis and conducted at one institution, we investigate the epistemological, structural, and relational factors that shape ID doctoral research supervision, explore how differing knowledge cultures and values are negotiated in supervisory practices, and consider how established structures and discourses influence the processes and outcomes of these supervisory relationships.